Konsep Pembinaan Keluarga Sakinah terhadap Narapidana Perempuan di Lapas Kelas II A Bandung - Yusrina Mardhiyah Sabila; Shindu Irwansyah; Ilham Mujahid (Bandung Conference Series: Islamic Family Law, 2022)
Abstract. In Bandung Sukamiskin Prison there are 400 female inmates. This figure is quite a large number, that not only men who commit crimes, but also many women who are involved in criminal acts. The purpose of this study was to determine the concept of fostering a sakinah family against female prisoners in Class II prisons in Bandung. This research is a qualitative research. This study has a technique of collecting data with interviews, observation and documentation. Respondents in this study were Islamic religious instructors totaling 1 person and 2 female prisoners. The results of this research are 1) The concept of implementing the Sakinah family development activities for the inmates of the Women's Prison II A Bandung has been conceptualized based on the concept of spiritual (religious) development where the implementation of the concept of fostering the Sakinah family is carried out by reading the Koran, praying, memorizing surahs, then studying and etiquette in married. 2) The process of implementing the development of the Sakinah family at the Sukamiskin Prison in Bandung is carried out by providing romance booths so that the rights as husband and wife of inmates can be carried out and this guidance is carried out to overcome inmates' problems related to problems in the family. 3) The impact resulting from fostering the Sakinah family is that inmates can take positive things where they can recite the Koran, pray, study sunnah, and etiquette in the household even though they are prisoners. Meanwhile, because the study of the development of the Sakinah family was the only material, the prisoners were bored and thought of it as just filling their free time. Abstrak. Dalam Lapas Sukamiskin Bandung terdapat 400 orang Narapidana Perempuan. Angka tersebut merupakan jumlah yang cukup banyak, bahwa tidak hanya pria saja yang melakukan tindak kriminalitas, namun perempuan pun tidak sedikit yang terlibat dalam tindak kriminalitas. Tujuan penelitian ini adalah untuk mengetahui konsep pembinaan keluarga sakinah terhadap narapidana Perempuan di Lapas Kelas II Bandung. Penelitian ini adalah penelitian kualitatif. Penelitian ini memiliki teknik pengumpul data dengan wawancara, observasi dan dokumentasi. Responden dalam penelitian ini adalah penyuluh agama islam berjumlah 1 orang dan 2 orang narapidana perempuan. Hasil peneltian ini adalah 1) Konsep pelaksanaan kegiatan pembinaan keluarga Sakinah pada warga binaan Lapas Perempuan II A Bandung sudah terkonsep dengan berlandaskan konsep pembinaan rohani (keagamaan) dimana pelaksanaan konsep pembinaan keluarga sakinah dilakukan dengan mengaji, shalat, menghafal surah, kemudian kajian dan adab dalam berumah tangaa. 2) Proses pelaksanaan pembinaan keluarga Sakinah di Lapas Sukamiskin Bandung dilakukan dengan penyediaan bilik asmara agar hak sebagai suami istri narapidana dapat terlaksana dan pembinaan ini dilakukan untuk mengatasi masalah narapidana terkait masalah dalam keluarga. 3) Dampak yang dihasilkan dari pembinaan keluarga Sakinah adalah narapidana dapat mengambil hal positif dimana dapat mengaji, shalat, kajian sunah, dan adab dalam berumah tangga meski menjadi tahanan. Sementara itu karena kajian pembinaan keluarga Sakinah itu saja materinya sehingga narapidana bosan dan mengganggap sebagai mengisi waktu kosong saja.